Emotions spread like contagious diseases - Hao Liu; Dong Zhang; Yaning Zhu; Hongwen Ma; Hongling Xiao (Frontiers in Psychology)
Emotional contagion, that is, the spontaneous synchronization of emotions among individuals, is the basic mechanism of social cohesion and survival of different species. Emotional contagion can be observed in humans and many animals, and it has become an effective means to protect individuals from danger. The study of emotional contagion in different animals is of evolutionary significance, and in human society, emotional contagion has an important impact on mental health and group behavior. However, the existing research still has obvious shortcomings in the similarities and differences of cross-species emotional contagion, the communication dynamics in virtual space and the infectious effect of positive emotions. This paper reviews the mechanisms of emotional contagion in different species, such as rodents, nonhuman primates, dogs, crows and zebrafish, highlighting evolutionary conservatism and species-specific adaptation, and analyzes the role of human children's behavioral mimicry in its early development. Furthermore, we extend the discussion of emotional contagion to virtual social networks, revealing the unique communication mechanism in online environment. In addition, by combing the sociological model and the emerging neurocognitive model, the complex process of emotional contagion can be explained more comprehensively. Through multidisciplinary perspective, it provides systematic theoretical and empirical support for us to understand emotional contagion.